Characterization of Staphylococcus aureus in a Pediatric Burn Unit - Smith, Rodney F. (1973)
A one-year study on an endemic strain of Staphylococcus aureus phage type 84/85 in a children's burn unit is described. The endemic strain rapidly colonized the burns and nares of acute patients after admission but was not isolated from a patient on admission. Nonendemic strains of S. aureus found on some new patients were mostly non-phage typable and did not prevail in burns. The endemic strain was rarely isolated from the nares and skin of reconstructive patients or from the nares of hospital personnel. The endemic strain did colonize the oral cavity, normal skin, and intestinal tract of some acute patients. Endemic and nonendemic strains of S. aureus from the burned children were compared in their biochemical activities and antibiotic sensitivities to two groups of S. aureus from one other local and one Danish burns unit. The latter groups of strains represented different combinations of staphylococcal phage group III strains. Each of the four groups of strains differed in production of hemolysins, Tween 80 hydrolysis, egg yolk reaction, and proteolysis of casein and gelatin. All of the strains were uniformly sensitive to gentamicin, oxacillin, and cephalothin. Only 4 of 162 strains tested were methicillin resistant. The endemic S. aureus strains of phage type 84/85 were uniformly resistant to eight other antibiotics including lincomycin and clindamycin. The endemic strain was not the known cause of a clinically documented infection in a group of 82 acute patients studied. The possible role of S. aureus strains of phage group III in burn grafting problems is discussed.